Physiological causes for decreased productivity under high salinity in Boma, a tetraploid Chloris gayana cultivar - De Luca, Marcos Javier; García Seffino, L.; Grunberg, Karina; Salgado, M.; Córdoba, Alicia R.; Luna, Celina Mercedes; Ortega, Leandro Ismael; Rodriguez, Andrés Alberto; Castagnaro, Ana P.; Taleisnik, Edith (CSIRO Publishing, 2020)
Rhodes grass (Chloris gayana Kunth) is widely cultivated in the semi-arid tropics and favoured for salt tolerance; nevertheless, productivity decreases significantly under saline conditions, especially in tetraploid cultivars. The purpose of this work was to explore, in the tetraploid cultivar Boma, the physiological causes for such decrease. Experiments were carried out in vegetative plants in the greenhouse. At high salinity (200 mM NaCl), an early reduction in leaf area expansion was observed, and, later, decreased dry matter accumulation, suggesting that the central effect of salinity was a limitation of leaf growth. This was evaluated in 2 closely related Boma clones, exhibiting different degrees of salt tolerance. Growth, ion accumulation and excretion, sugars, and proline concentrations were measured under a range of salt concentrations (0–200 mM NaCl). Differences between the clones in leaf expansion were expressed only at high salinity, but were not associated with differences in water potential or hydraulic conductance in the expanding region. At all salinity levels, the proportion of dry leaves was higher in the clone which also had lower salt gland density and Na excretion rates. Less efficient Na extrusion, associated with high oxidative stress, may be the main cause for leaf senescence and differences in productivity between these clones.